Talent Management, Development, and Retention of Generation Y Employees in New Zealand Clinical Laboratory - Lau, Kin Ming Oscar (Auckland University of Technology, 2024)
Laboratory science is an integral component of the healthcare system and relies on a skilled workforce to prevent, diagnose, and treat diseases. In New Zealand, the medical laboratory profession comprises various professionals regulated under the Health Practitioners Competence Assurance Act 2003. The industry has witnessed a transformative shift, reflecting changing ideologies and values across generational groups, notably with the influx of Generation Y employees. Despite anecdotal evidence pointing to retention challenges, systematic research on talent management's impact on Generation Y employees in New Zealand's clinical laboratory sector is scarce. To address this gap, the study aims to identify factors contributing to Generation Y employee retention and develop a conceptual framework to enhance retention within clinical laboratories. A total of 143 Generation Y employees from diagnostic laboratories participated in this study. The data were analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method with SmartPLS 4 software. The results showed that talent management practices, including mentoring, strategic leadership, and competency development, positively influence the intention of Generation Y employees to stay in their roles. In contrast, knowledge sharing does not significantly impact their intention to stay. Moreover, the study explored how competency development mediates the relationships between mentoring, strategic leadership, and knowledge sharing concerning participants’ intention to stay within the organisation. Results showed that mentoring and strategic leadership indirectly affect the intention to stay through competency development. Although marginally significant, the anticipated mediation effect of knowledge sharing is not fully supported, highlighting the complex relationship between knowledge sharing initiatives and employee retention. These nuanced findings emphasise the need for tailored and innovative retention strategies, acknowledging the multifaceted decision-making processes of Generation Y employees and the necessity for innovative retention strategies. In addition to the empirical insights, the study presents a conceptual framework grounded in empirical data and theoretical foundations. This framework serves as a foundation for organisations aiming to create a supportive work environment that fosters the commitment and longevity of their Generation Y workforce. By delving into the distinctive dynamics of New Zealand's clinical laboratory sector, this study contributes valuable knowledge to the broader field of workforce management, paving the way for enhanced talent retention strategies in allied health professions.